Interactive Visual Auditory Kinesthetic-Based E-Module to Enhance Elementary School Students’ Learning Outcomes - Suriantara, I Gede; Sanjaya, Putu; Lisna Handayani, Ni Nyoman (Jayapangus Press, 2025)
This study aims to design an e-module that integrates visual auditory and kinesthetic approaches to teaching sixth-grade elementary school students about the properties of magnets in everyday life, using criteria that are valid, practical and effective in improving learning achievement. This study uses Thiagarajan's 4D model, which consists of four stages Define, Design, Develop and Disseminate. Data were collected through questionnaires and multiple-choice tests. Data analysis included quantitative and qualitative descriptive approaches, as well as inferential statistical analysis using the t-test. The validity of the module was evaluated using Gregory's formula, practicality was calculated using the mean value, while effectiveness was tested using an independent sample t-test. The results of the study indicate that the e-module is highly valid (Aiken's V = 1.00), highly practical (average practicality score = 67.6), and effective in improving student learning outcomes (t = 3.797; p < 0.05; effect size = 1.39). This visual-auditory-kinesthetic-based e-module is suitable for use as a learning medium to improve the learning outcomes of sixth-grade elementary school students.